Fihrist-i nusakh-i khatti-i Farsi-i ganjinah-i anstitu-i sharqshinasi-i Abu Rayhan Biruni - Tashkant / . The list of the Persian manuscript of the treasury of Abu Raiyhan Beeroni (Vizarat-i Umur-i Kharijah. Markaz-i Chap va Intisharat)
1.1 : Tarikh. - 118 p.